2016
DOI: 10.5937/savteh1601053t
|View full text |Cite
|
Sign up to set email alerts
|

Citric acid-based deep eutectic solvents: Physical properties and their use as cosolvents in sulphuric acid-catalysed ethanolysis of oleic acid

Abstract: Deep eutectic solvents (DESs) are noted to be green ionic liquid (IL) analogues, and their many favourable properties made them interesting for the scientific community. In this study, two novel DESs of citric acid with the monosaccharides D-glucose or D-fructose (1:1 molar ratio) were prepared and characterized. At the atmospheric pressure, the density, the dynamic viscosity, and the electrical conductivity of these eutectic solvents were measured and analysed as the function of temperature in the practical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Shear flow behavior of NADES Flowability of NADES under varied shear rates depend on the apparent viscosity indicating their expected field of application and uses (Elhamarnah et al 2019). The flow behavior of NADES at room temperature has advantages over traditional solvents, so that they can be more easily used and operated in different industrial conditions (Troter et al 2016;Paiva, Matias, and Duarte 2018). The rheological behavior of different mixtures of NADES at room temperature is showing a universal trend depending on the detailed microstructure of the HBD and HBA.…”
Section: Rheological Behavior Of Nadesmentioning
confidence: 99%
See 1 more Smart Citation
“…Shear flow behavior of NADES Flowability of NADES under varied shear rates depend on the apparent viscosity indicating their expected field of application and uses (Elhamarnah et al 2019). The flow behavior of NADES at room temperature has advantages over traditional solvents, so that they can be more easily used and operated in different industrial conditions (Troter et al 2016;Paiva, Matias, and Duarte 2018). The rheological behavior of different mixtures of NADES at room temperature is showing a universal trend depending on the detailed microstructure of the HBD and HBA.…”
Section: Rheological Behavior Of Nadesmentioning
confidence: 99%
“…However, NADES may behave as Newtonian fluids as well, independently of shear rate (Elhamarnah et al 2019;R€ uther et al 2013;Cao et al 2016;Aroso et al 2017). Troter et al (2016) reported a shear-thinning behavior of citric acid:glucose and choline chloride:citric acid at 1:1 molar ratios in the temperature range of 293.15-363.15 K at atmospheric pressure within the shear rate of 0.1-1000 s À1 . Sheer thinning behavior of choline chloride:lactic acid, choline chloride:citric acid, choline chloride:malic acid, choline chloride:lactic acid and choline chloride:fructose NADES was also observed by Altamash et al (2017) at 25 C under a shear rate domain of 0.01-1000 s À1 at atmospheric pressure.…”
Section: Rheological Behavior Of Nadesmentioning
confidence: 99%
“…The properties of the prepared DESs at room temperature are given in Table 1. The physical and thermodynamic properties of the ChCland citric acid-based DESs can be found elsewhere [6,20].…”
Section: Preparation Of Dessmentioning
confidence: 99%
“…In addition, density values can be used to calculate values of thermal expansion or compressibility coefficients that are valuable liquid structure and interactions data. When a DES system is heated, the molecules move faster, increasing the molar volume and, thus, decreasing the density [34]. Although high density of a DES is a problem for handling or mixing in chemical processes, it may be desirable in extraction processes since a relatively large difference in density between the raffinate and extract phases is required to guarantee more efficient phase separation [26].…”
Section: Resultsmentioning
confidence: 99%